GETTING STARTED IN INTERNAL SOCIAL RESPONSIBILITY: EVALUATION OF INTEGRATION BETWEEN SOCIAL ACCOUNTING AUDIT AND INTERNAL CORPORATE SOCIAL RESPONSIBILITY: REVIEW OF LITERATURE - Sanusi, Fasilat Aramide; Johl, Satirenjit Kaur; Taibat, Akanbi (International Journal of Psychosocial Rehabilitation, 2020)
Social accounting and audit and internal corporate social responsibility are similar concepts that share equal value within the sphere of social activities. However, a comprehensive review that portray understanding of academic concept alongside other non-academic event that influence social expectations with respect to employee as an internal stakeholder is missing in the existing studies. The purpose of this paper is to examine social integration that exist between social accounting and audit and internal corporate social responsibility by reviewing the most relevant information that have contributed to their understanding and definitions. It should be noted that the integration of the two concepts continue to be the subject to multiple perceptions. The analysis conducted shed light on the group of issues that emerged with regards to politics, economic and stakeholder’s interests which must be continuously explore in order to respond to social demand of employees with respect to job. Social accounting and audit and internal corporate social responsibility is expected to remain part of organization’s sustainable development. Therefore, there is plausible future for social accounting and audit and internal corporate social responsibility if considerable attention is given to their integrative approach.